Toxoplasma infection during pregnancy. Counselling and screening challenges - Laura Dumitrasi (Romanian Journal of Infectious Diseases, 2020)
Toxoplasmosis is the most common cause of congenital infection, causing long term ocular and neurological lesions with relapses during childhood and adolescence. The risk of congenital infection is highest after primary maternal infection with advancing maternal gestation. Only a few european countries recommend a routine prenatal screening although therapeutic options are the same. Primary prevention measures regarding food hygiene and secondary prevention through serological testing are the most important ways to prevent and detect toxoplasmosis during pregnancy. Counselling is challenging since there is a need for reference centers of diagnosis. In Romania there is a routine clinical practice to offer screening through the TORCH panel in the first trimester of pregnancy. This review summarizes the current methods of diagnosis and management of toxoplasmosis in pregnancy.